New canine parvovirus 2a infection in an imported Asian small-clawed otter (Aonyx cinereus) in Japan - TAMUKAI, Kenichi (J Vet Med Sci, 2021)
Post-import from the Republic of Indonesia to Japan in 2017, two juvenile, captive bred Asian small-clawed otters (Aonyx cinereus) exhibited gastrointestinal symptoms, including vomiting, diarrhea, and hematemesis, and died. One of them was examined postmortem. Microscopically, the small intestinal mucosa was necrotic with crypts lined by regenerating large epithelial cells. A gastric cardiac mucosal ulcerative lesion containing fungal yeasts and pseudohyphae morphologically indicated Candida spp. The lymph nodes exhibited marked lymphoid depletion. Canine parvovirus 2 (CPV-2) was isolated from an oral swab, and virus protein 2 (VP2) gene sequencing revealed new CPV-2a. To our knowledge, this is the first new CPV-2a infection report in Asian small-clawed otters. This infection should be considered in gastrointestinal symptom-related cases in this species.